Performance of flexible dye-sensitized solar cell (FDSSC) using flexible substrate at different angles under back-illumination configurations - Mohd Ismail, Izad Syahrul Ariffin; Shafiee, Farah Nabilah; Hamidon, Mohd Nizar; Shafie, Suhaidi (Springer, 2024)
This research presents the development of a flexible dye-sensitized solar cell (FDSSC) based on titanium (Ti) foil as the photoanode and indium tin oxide-coated polyethylene terephthalate (ITO-PET) as the counter electrode (CE). The FDSSC was fabricated using the doctor blade method with excellent flexibility and mechanical durability. The performance of the FDSSC was evaluated under a solar simulator, analysing its essential photovoltaic parameters. The results showed that the developed FDSSC has high conversion efficiency of 2.03 and good performance stability from 0° to 20° in the angle bending test. In addition, the surface of the photoanode substrate was analysed at varying angles from 0° to 50°. The findings from this research indicate that the FDSSC has the potential to be used in next-generation applications, where it can be mounted in a variety of orientations, including curved or irregular surfaces, which can improve power conversion efficiency. This flexibility allows the FDSSC to capture sunlight from various angles to achieve maximum exposure to solar irradiance throughout the day.